Evolución diagenética de los carbonatos arrecifales de la Formación Torrecilla en Cameros y de los carbonatos continentales suprayacentes (Kimmeridgiense inferior-Titónico) en el Sector de Soria. Cuenca de Cameros, N. España - Mas, R.; Benito, M. I. (Journal of Iberian Geology, 2002)
The last marine Jurassic unit deposited in the Soria area corresponds to the Torrecilla en Cameros Fm. (Early Kimmeridgian). This unit, composed of sandstones and reefal and oolitic limestones, was deposited in a shallow carbonate ramp. The synsedimentary diagenetic processes of micritization and precipitation of peloidal micrite and fibrous calcite occurred during the episode of sedimentation. In the Late Kimmeridgian the reefal unit was subaerial exposed and was affected by the meteoric waters which led to the dissolution and neomorphism of aragonite and HMC and the precipitation of a generation of meteoric calcite. The top of the unit was also edaphized and a ferruginous crust was developed. The episode of rifting, that led to the formation of the Cameros Basin, occurred from the Tithonian and during the Early Cretaceous. In this sector, the sedimentation of the basin, mainly continental, started with the deposition of the Ágreda Aloformation. Carbonates deposited of the base of this continental unit have elemental and isotopic features very similar to those of the meteoric cements precipitated in the reefal unit. This suggests that the environmental conditions were very similar during precipitation of meteoric carbonates in both units.With the progressive burial, precipitation of a ferroan calcite cement occurred in fractures and remaining porosity in both units. Later, a generation of saddle ankerite precipitated, perhaps in relation to the hydrothermal metamorphism that affected the northeastern sector of the basin during the Middle-Late Cretaceous. Lastly, the precipitation of a generation of nonferroan and Mg-rich calcite cement occurred, possibly during the Latest Cretaceous. The last preserved diagenetic stages were related to the tectonic uplift of the region during the alpine compression, and the exhumation of the reefal unit during which ankerite and ferroan calcite were replaced by nonferroan, inclusion rich calcite.